How patients' representations of cystic fibrosis-related diabetes inform their health behaviours. Issue 10 (2nd October 2016) - Sylvain, Chantal; Lamothe, Lise; Berthiaume, Yves; Rabasa-Lhoret, Rémi
Abstract : Background: Although diabetes is a frequent complication of cystic fibrosis (CF), patients' behaviours tend not to comply with best practice recommendations. Using Leventhal's Common-Sense Model, we address this issue by exploring patients' representations of CF-related diabetes (CFRD) to better understand the discrepancy between patients' expected and observed health behaviours. Methods: Semi-structured individual interviews were conducted with patients ( n = 39) in six CF clinics in Quebec, Canada. These interviews were part of a larger research project on screening and management practices for CFRD. Results: Illness representations differed between two groups of interviewed patients: (1) one group had either CF without dysglycemia or CF with impaired glucose tolerance; and (2) the other group had CFRD. Both representations were internally consistent and encompassed Leventhal's five dimensions of illness representation: illness identity, cause, timeline, consequences and control. Conclusions: Patients require specific information on CFRD. The screening phase could be a crucial time to help patients adjust their representations to fit the reality of CFRD.